Artificial intelligence in social media: a systematic review of trends - Danendra, I Kadek Aryasatya; Latupeirissa, Jonathan Jacob Paul (Jurnal Studi Komunikasi, 2025)
This systematic literature review addresses critical gaps in understanding AI's role in social media communication strategies, specifically examining its impact on influencer marketing, crisis communication, and human-centred trust-building methodologies. Informed by conceptual frameworks of information ethics, user trust, and algorithmic influence, the study distinguishes itself by focusing on recent advancements in fairness-aware machine learning, AI-driven fact-checking, and evolving regulatory landscapes. Analysing 30 peer-reviewed Scopus articles from 2020 to 2025, this study employs a systematic literature review methodology guided by the PRISMA guidelines to ensure rigorous selection and analysis of relevant studies. Findings reveal AI's transformative potential in personalisation and efficiency, yet expose critical ethical challenges like AI-driven deepfakes, algorithmic polarisation, and privacy concerns. It is recommended to develop AI transparency mechanisms, accountability frameworks for public service algorithms, and targeted training for content detection by citizens, as well as provide practical guidance for responsible AI integration in digital communications.